THE STUDY OF LEXICAL AND SYNTACTIC AMBIGUITY IN PUNS POSTED BY @THE.LANGUAGE.NERDS ON INSTAGRAM - Dina Sayyidina Rani; M. Aries Taufiq; Rizky Arif Afandi (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Pun– also known as paronomasia, a humorous play on words, is one of language phenomenon that has been used ubiquitously. A lot of people have been using puns to create humor by utilizing the ambiguity that inherent in them. Thus, this research aims to identify the ambiguity both lexical and syntactical in puns, which is the prerequisite of puns themselves. By using qualitative descriptive research, the researcher took the data from an Instagram account that heed of language matters, namely @the.language.nerds. From 20 data, the researcher found 16 lexical ambiguity and 4 syntactic ambiguity in the puns posted by @the.language.nerds during July 2nd, 2021 – December 2nd, 2022. The results showed that the puns contained lexical ambiguity is commonly used as the language tools to create the humor than syntactic ambiguity. The results also showed the difference interpretation of meanings contained in each pun.